Barriers to English housing energy efficiency: stakeholders' perspectives. (2015) - Thakore, Renuka; Goulding, Jack; Toogood, Mark
Sustainable transformation to energy efficient housing remains very challenging. While implementing effective governance remains specific to local and global contexts, more encompassing interrelated essential conditions have emerged which serve as prerequisite to varying degrees in implementing strategies for energy efficient housing in Europe. Notably, the existing English housing system has incorporated these critical drivers to leverage effective governance for energy efficient housing environments. Whilst these are important, there is a paucity of work on the understanding of 'barriers' against the backdrop of these prerequisite essential conditions from the whole system-wide stakeholders' perspectives. The purpose of this paper is to address these issues and identify a list of correlated and commonly agreed barriers from the stakeholders' perspectives. From the initial set of 40 barriers, this research identifies ten, as prioritised by online survey respondents. The paper, therefore, directs future research to investigate strategies that can overcome these key barriers.